The Impact of Human Resource Management on Awareness Employee and Organization - Watanyar, Abdul Basir; Bashar, Hanifullah; Ghorbandi, Nangyalai (Integrated Journal for Research in Arts and Humanities, 2024)
The study aims to investigate the impact of Human Resource Management (HRM) on employee awareness and organizational capacity within the Afghanistan International Bank (AIB). A positive workplace culture, characterized by clear and accurate communication, is essential for employees to perform their duties effectively. Misunderstandings and inefficiencies often arise from unclear communication and inadequate HRM practices. The primary research question guiding this study is: "What is the impact of HRM on employees' awareness and organizational capacity at AIB?" Sub-questions include: "How does HRM influence employee productivity?" and "What is the effect of HRM on employee efficiency?" The hypotheses posit that HRM positively impacts employee awareness, organizational capacity, productivity, and efficiency. Methodologically, the study employs both primary and secondary data collection techniques. Primary data were gathered through the distribution of 50 questionnaires to AIB employees in Kabul, utilizing a Likert scale to measure responses. Secondary data were sourced from related articles, electronic websites, journals, and research reports. Random sampling techniques were used to select participants who were properly briefed on completing the questionnaires. The findings indicate that HRM significantly enhances employee productivity, awareness, and organizational capacity at AIB. Additionally, HRM improves daily operational efficiency, customer service quality, and the effectiveness of information systems. By addressing previous organizational challenges, HRM enables employees to maximize the benefits from increased awareness and capacity, ultimately contributing to the bank's overall performance.